High Frequency of Intravenous Injection of Human Adipose Stem Cell Conditioned Medium Improved Embryo Development of Mice in Advanced Maternal Age through Antioxidant Effects - Kihae Ra; Hyun Ju Oh; Geon A Kim; Sung Keun Kang; Jeong Chan Ra; Byeong Chun Lee (Animals, 2020)
Advanced maternal age (AMA) has become prevalent globally. With aging, weakened antioxidant defense causes loss of normal function in the ovary and uterus due to oxidative stress. Here, we aimed to improve embryo development in AMA mice by intravenous injection (IV) of human adipose stem cell conditioned medium (ASC-CM) at various frequencies and intervals as an antioxidant intervention. Four- and six-month-old female ICR (Institute of Cancer Research) mice were randomly divided into groups IV treated with human ASC-CM under different conditions, and in vitro and in vivo embryo development were evaluated. Consequently, compared to the control group, blastocyst formation rate of parthenotes was significantly promoted in 4-month-old mice and the mean number of implanted fetuses after natural mating was significantly increased by approximately two-fold in 6-month-old mice. Through gene analysis, the anti-apoptotic and anti-oxidative effects of human ASC-CMs were confirmed in the ovaries and uterus of pregnant mice at both ages. In particular, ovarian expression of gpx1 and catalase drastically increased in 6-month-old mice. Furthermore, the levels of gpx1 and catalase were further increased, with a high frequency of injection regardless of age. Thus, we demonstrated for the first time the anti-oxidative effect of human ASC-CM administration against ovarian aging and the optimal injection condition.